Analisis Faktor yang Mempengaruhi Keberhasilan Sistem Informasi Pendaftaran Online di Rumah Sakit Nasional Diponegoro Kota Semarang - Ni Made Deviana Widiantari; Sutopo Patria Jati; Rani Tiyas Budiyanti (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
The development of online-based information technology in the health sector can improve the quality of hospital services. Currently, Diponegoro National Hospital has implemented outpatient registration based on the